UFW union meeting in Fresno - Manuel Echavarria:::photographer::: (2025)
Members of the Santa Maria chapter get a national perspective when they attend their first UFW union meeting in Fresno. Miembros de la UFW de la región de Santa Maria pudieron apreciar una perspectiva nacional cuando asistieron a su primera reunión con la UFW en Fresno.